Insights into the salinity tolerance of the succulent halophyte Arthrocnemum macrostachyum: comparative ecophysiology of plants from heteromorphic seeds - Nisar, Farah; Hameed, Abdul; Gul, Bilquees; Aziz, Irfan; Nielsen, Brent L. (Frontiers in Plant Science, 2024)
Little is known about the similarities and differences in responses of plants grown from heteromorphic seeds, which are morpho-physiologically dissimilar seeds produced simultaneously on the same plant. In this context, we studied how plants grown from heteromorphic (i.e. black and brown) seeds of the succulent halophyte Arthrocnemum macrostachyum respond to increasing salt levels during growth by modulating their physiochemical processes. Plants germinated from both black and brown seeds did not show any significant growth reduction, while chlorophyll a content declined at moderate salinity (300 mM NaCl) compared to non-saline controls. High salinity (900 mM NaCl), on the other hand, caused decreased growth and sap ψs in plants derived from either seed type. In plants emerged from brown but not black seeds, high salinity increased the activity of all H2O2-detoxifying antioxidant enzymes as well as GSH level. Under conditions of high salinity, plants obtained from both types of seeds exhibited signs of lipid peroxidation in the form of elevated 2 malondialdehyde levels. Our findings thus point to metabolic variablity in A. macrostachyum plants growing from heteromorphic seeds under salt stress.